Penerapan Metode Probing Promting Pada Mata Pelajaran Fiqih Dalam Meningkatkan Motivasi Belajar Siswa Kelas VIII MTs Tarbiyah Waladiyah Pulau Banyak - Ahmad Fuadi; Usmaidar Usmaidar; Yuliana Yuliana (Reslaj : Religion Education Social Laa Roiba Journal, 2019)
Ahmad Fuadi1 , Usmaidar2, Yuliana3 Sekolah Tinggi Agama Islam Jam’iyah Mahmudiyah Tanjung Pura1,2,3 Email : Ahmad_Fuadi@staijm.ac.id1 , usmaidar_12@staijm.ac.id2 ABSTRACT The learning method of Probing Promting is "Learning by means of the teacher presenting a series of statements that are guiding and digging so that a thought process occurs which links each student's knowledge and experience with the new knowledge that is being learned. With this learning model the question and answer process is carried out by randomly assigning students so that each student inevitably has to participate actively, students cannot avoid the learning process, at any time they can be involved in the question and answer process. With this learning model the question and answer process is carried out by randomly assigning students so that each student inevitably has to participate actively, students cannot avoid the learning process, at any time they can be involved in the question and answer process. The definition of motivation is the change in energy in a person which is marked by the emergence of feelings and is preceded by a response to a goal. A series of activities carried out by each party or individual is actually motivated by something or what is generally called motivation. Motivation is what encourages them to carry out an activity or job. it is this motivation that a person will be more successful in a lesson. So, motivation will always determine the intensity of learning efforts for students. And it needs to be emphasized that motivation is closely related to goals. To support the interest in learning for each individual, there must be motivation in learning, because that motivation will move the person to do something, in this case, learning. With diligent effort and primarily based on motivation, someone who learns will be able to produce good achievements. The intensity of a student's motivation will greatly determine the level of learning achievement. Keywords: Probing Promting Method, Learning Motivation, Fiqh Lessons